THE MARINE STEREOSCOPIC CAMERA UNIT MSA-1 - Vinogradov,V. V. (1968)
The paper describes the design of a new device for stereoscopic photography of ocean waves. The device is designed for obtaining stereopairs and for taking a sequential strip of pictures. The data include types of lenses, focal lengths, film size and capacity, angle of view, type of shutter, and other facts. The camera arrangement was used on two spring-summer excursions into the North Atlantic. A series of recommendations is made in regard to power source, types of film arrangement of the camera setup on the ship, and related problems. Edited trans. of Okeanologiya (USSR) v4 n5 p896-899 1964, by D. Drury.